2011
DOI: 10.1167/iovs.10-6549
|View full text |Cite
|
Sign up to set email alerts
|

Cone Structure in Retinal Degeneration Associated with Mutations in theperipherin/RDSGene

Abstract: peripherin/RDS mutations produced diffuse AF abnormalities, disruption of the photoreceptor/RPE junction, and increased cone spacing, consistent with cone loss in the macula. The abnormalities observed suggest that the integrity of the second intradiscal domain of peripherin/RDS is critical for normal macular cone structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 46 publications
2
34
0
1
Order By: Relevance
“…6 The in vivo measurement of cone photoreceptors with AOSLO has been used to assess cone structure in normal subjects and patients with retinal degenerations. 10,13,[20][21][22][23] The reproducibility of AOSLO measures in the present study, as graded by two experienced independent readers, was high. Cone density was calculated from cone spacing assuming a hexagonal packing of the cone mosaic.…”
Section: Discussionmentioning
confidence: 88%
“…6 The in vivo measurement of cone photoreceptors with AOSLO has been used to assess cone structure in normal subjects and patients with retinal degenerations. 10,13,[20][21][22][23] The reproducibility of AOSLO measures in the present study, as graded by two experienced independent readers, was high. Cone density was calculated from cone spacing assuming a hexagonal packing of the cone mosaic.…”
Section: Discussionmentioning
confidence: 88%
“…Although previous studies 34,35,[41][42][43][44][45][46][47][48][49][50][51][52] have used AOSLO to assess cone spacing and density in normal and diseased eyes, none have reported on how foveal cone measures and visual function are correlated. The present study demonstrates a significant correlation between increased AOSLO cone spacing Z-scores and decreased VA at or near the fovea, as well as a significant correlation between Z-scores and foveal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,[41][42][43][44][45][46][47][48][49][50][51][52] Adaptive optics-based studies 41,42 of retinal degeneration showed a significant correlation between macular cone spacing and central visual function, but given the small size and unique anatomy 53 of foveal cones and the resulting difficulties posed on imaging, 54 these studies were unable to assess cone morphology at the foveal center. Within the past few years, advanced systems that have implemented improvements in AO scanning laser ophthalmoscopy (AOSLO) system design 55 and advanced controls 56 have been able to more routinely visualize the foveal cone mosaic.…”
mentioning
confidence: 99%
“…14 This technique has allowed noninvasive observation of the individual photoreceptors in patients with retinal disease. [15][16][17][18][19][20][21][22] Combined, data from the various highresolution imaging modalities can provide a thorough assess- …”
mentioning
confidence: 99%